2016
DOI: 10.1016/j.aott.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Regression of a symptomatic thoracic disc herniation with a calcified intervertebral disc component

Abstract: There were only a few cases describing spontaneous regression of calcified thoracic disc herniation in the literature. We present a 38-year-old male office worker who had left paramedian-foraminal extruded disc at T7–T8 with calcifications of the T7–T8 and T8–T9 intervertebral discs. This case was unique in that the non-calcified extruded disc material regressed almost completely in 5 months while the calcified intervertebral discs remained the same during the process of regression. This report stresses that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Complete spontaneous regression of TDHs has been described previously in the literature; however, none of these TDH were giant and none was caused by a trauma (►Table 1). [9][10][11][12][13][14][15][16] Our case is the first documented acute traumatic and spontaneously regressing TDH: the neuroradiological finding of a herniated disk being nonadherent to the posterior longitudinal ligament and dura with only minimal calcification plus the acute onset of symptoms after a major trauma are suggestive of posttraumatic disk herniation. To our knowledge, only nine cases of spontaneous TDH regression have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Complete spontaneous regression of TDHs has been described previously in the literature; however, none of these TDH were giant and none was caused by a trauma (►Table 1). [9][10][11][12][13][14][15][16] Our case is the first documented acute traumatic and spontaneously regressing TDH: the neuroradiological finding of a herniated disk being nonadherent to the posterior longitudinal ligament and dura with only minimal calcification plus the acute onset of symptoms after a major trauma are suggestive of posttraumatic disk herniation. To our knowledge, only nine cases of spontaneous TDH regression have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the published studies of calcification of nucleus pulposus and/or calcific discitis in adults [Table 1]. [12345678910121314151617181920212223242526] The collected data in this literature review included demographic data (i.e., gender and age of the patient), level of involving spine, symptoms of patient, location or extension of calcified disc, probably precipitating event, the presence of bone marrow edema on MRI, the occurrence and follow-up time of spontaneous regression, treatment, and outcome of patient.…”
Section: Discussionmentioning
confidence: 99%
“…[29] On the other hand, some studies found that symptomatic calcified herniated disc totally regressed, while asymptomatic calcified disc or intradiscal calcification was not absorbed and still remained in place. [4519]…”
Section: Discussionmentioning
confidence: 99%
“…3 There are some cases of spontaneous regression of this disease but the gold standard for treatment of symptomatic CCTDH is surgical resection. 9 CCTDH presents a surgical difficulty as intradural lesion are frequently encountered with high rate of adhesion to the dura, 10 generating unacceptable rates of cerebrospinal fluid leaks that are difficult to manage with minimally invasive techniques (thoracoscopy, mini-open thoracotomy). 10,11 Conversion to open procedures is thus required with increased morbidity of these approaches.…”
Section: Introductionmentioning
confidence: 99%